If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+9)=42
We simplify the equation to the form, which is simple to understand
3(x+9)=42
Reorder the terms in parentheses
+(+3x+27)=42
Remove unnecessary parentheses
+3x+27=+42
We move all terms containing x to the left and all other terms to the right.
+3x=+42-27
We simplify left and right side of the equation.
+3x=+15
We divide both sides of the equation by 3 to get x.
x=5
| X^6+5x^3-6=0 | | x(x)+5x+6=0 | | x(x)-5x-6=0 | | (3x^2-4x+10)-(x^2-9x+13)= | | c+150=1860 | | 5x(x)=6+2x | | x-13=-3 | | (2x^2-x+7)+(3x^2+x-9)= | | x(x)-7x-8=0 | | (40x)+(20*1.5x)=1625 | | 2-4y=4-5y | | 7y+3=6y-2 | | 6.4-2.1x=-77.4 | | x+y^2=0 | | 5-5x+8+2x+4x-4=3+2*5 | | x=1-y^2 | | 48=12-6n | | -2.3+m=-2.3 | | x-3/2=7/4 | | r+3.5=8 | | m(m)+6m-9=0 | | 20=10-5p | | 3(x)(x)-2x-5=0 | | (5x-5)(5x-5)= | | 15-39=-9 | | (7x^3-9x^2+5x)-(2x^2+3+6)= | | 2(x)(x)-3x-8=0 | | 40*12x=60x | | 25=7+3x | | 36x^2-12x+2=0 | | 5z-34=4z+4 | | cd^4-c^2d^6= |